Feasibility of an Adaptable Biorefinery Platform: Addressing the Delivery Scale Dilemma under Drought Risk. (February 2014) - Farmer, Michael C.; Benson, Aaron; Liu, Xiaolan; Capareda, Sergio; Middleton, Marty
Abstract : Conversion of biomass to electricity is often not economically feasible as a result of large transportation costs and low output prices. We build a model of an adaptable biorefinery situated at an agri-processing facility that already has biomass on-site and consider the optimal scale of the plant to achieve a price premium by selling peaking power given uncertain biomass deliveries year over year as a result of climatic variability. We find that, for conservative electricity prices, a plant situated near cotton gins in Texas could operate with positive expected net revenue while converting on average only 38% of available biomass for peak electricity prices.